IMPROVING STUDENTS’ SPEAKING SKILL THROUGH SHOW AND TELL METHOD AT GRADE IX STUDENTS OF PAX CHRISTI JUNIOR HIGH SCHOOL MANADO - Ignasius Mario Binioli; Tini Mogea; Merlin Maukar (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of the study is to prove whether or not Show and Tell method can improve students’ speaking skill. The research design used in this study is quasi-experimental method. The researcher used test as the instrument which in form of oral test consisted of pre-test and post-test. In pre-test, the researcher collected the data of students’ speaking fluency, comprehensibility, and accuracy. In post test, order to find out the progress of students speaking fluency, accuracy and comprehensibility of the treatment. The result is the mean score of pre-test in experimental group is 51,42. And the mean score of post-test in experimental group is 81,07. In the control group, the mean score of pre-test in control group is 49,33. And the mean score of post test in control group is 79,33. It can be concluded that the result of mean score increased after using Show and Tell method in order to improve students’ speaking skill.